Processes driving seasonal variability in DMS, DMSP, and DMSO concentrations and turnover in coastal Antarctic waters. (10th October 2016) - Asher, E. C.; Dacey, J. W. H.; Stukel, M.; Long, M. C.; Tortell, P. D.
Abstract: This study presents new measurements of the concentrations and turnover rates of dimethyl sulfide (DMS), dimethylsulfoniopropionate (DMSP), and dimethyl sulfoxide (DMSO) in coastal waters near Palmer Station, Antarctica, during the spring and summer of 2012–2013. Using several novel analytical and experimental techniques, we document variability in DMS, DMSP, and DMSO (DMS/P/O) concentrations and quantify dominant production and removal terms in the mixed layer DMS budget. Our results demonstrate considerable seasonal variability in the concentration of DMS (range 0–20 nM), total DMSP (8–160 nM), and total DMSO (4–160 nM). Over the seasonal cycle, dissolved DMSP concentrations were well correlated with total DMSP concentrations and the abundance of Phaeocystis antarctica, while DMSO concentrations (total and dissolved) were well correlated with DMS concentrations. DMSP cleavage from the dissolved pool (mean rate = 5.5 nM d −1 ) and release from microzooplankton grazing (mean 5.6 nM d −1 ) were the dominant sources of DMS, with smaller DMS production rates associated with DMSO reduction from the dissolved pool (mean 2.6 nM d −1 ) and krill grazing (mean 0.82 nM d −1 ). Specific rate constants for DMSP cleavage were inversely related to net primary production. Bacterial uptake was a primary contributor to DMS removal (mean −12 nM d −1 ), and we observed a significant correlation between bacterial production and gross DMS loss rate constants. Estimated sea‐air flux and photo‐oxidation constituted secondary DMS sinks. Our experimental and analytical methods provide insight into the DMS/P/O cycle at Palmer Station, and a starting point for future studies examining inter‐annual DMS/P/O variability in coastal Antarctic waters.